Peran Institusi Zakat Dan Wakaf Sebagai Pilar Dalam Sistem Perekonomian Indonesia - Asti Nur Wilda Ariza; Abdul Bahri Sukartono; Angga Teguh Susilo; Ade Gunawan; Muhammad Taufiq Abadi (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2024)
Zakat is the third pillar of Islam after reciting the shahada and praying and before fasting and Hajj. Because it is harmonious, the zakat service must be carried out by all Muslims in the world because it is an obligation. Zakat is a category of obligatory worship and social worship. This research uses qualitative research methods, namely literature study. This research explores previous primary data sources (books) that published articles/views and journals with research topics and focuses. A qualitative approach that uses an explicit literature review strategy. The results of this research show that zakat and waqf have a big influence on the Indonesian economy.